2017
DOI: 10.1002/ente.201600792
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Stability of Tailored CaMn0.875−xFexTi0.125O3−δ Perovskite Oxygen Carrier Materials for Chemical Looping Combustion

Abstract: CaMn1−xTixO3−δ are state‐of‐the‐art perovskite‐type oxygen‐carrier materials (OCMs) used in gaseous fluidized‐bed chemical looping combustion (CLC), which is currently undergoing upscaling and demo campaigns in several large pilot plants around the world. CLC requires control of oxygen release and uptake by the oxygen‐carrier material. The flexibility of the perovskite's structure allows a wide range of substitutions, which can be beneficial for tuning the properties. In this study, we investigate the benefici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Oxygen has been recognized as an essential chemical for power plants based on fossil fuel consumptions such as integrated gasification combined cycle and oxy‐fuel combustion, which have been recognized as the most realistic clean energy technologies for energy production with carbon capture and storage. Unfortunately, the current industrial tonnage oxygen production is still mainly achieved by the conventional cryogenic distillation technology, a very expensive technique .…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen has been recognized as an essential chemical for power plants based on fossil fuel consumptions such as integrated gasification combined cycle and oxy‐fuel combustion, which have been recognized as the most realistic clean energy technologies for energy production with carbon capture and storage. Unfortunately, the current industrial tonnage oxygen production is still mainly achieved by the conventional cryogenic distillation technology, a very expensive technique .…”
Section: Introductionmentioning
confidence: 99%
“…On A-site doping, partial substitution of the calcium by strontium, barium and lanthanum [12,13] is reported, as well as A-site-deficient compounds [14,15]. More relevant and interesting is the doping of the transition metal on the B-site, with partial substitution of manganese by magnesium, iron, titanium, or a combination of two or more of them [14][15][16][17][18][19][20][21][22][23][24][25]. Although it has limited miscibility in the perovskite structure, magnesium has positive catalytic effect on the methane reforming.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that it has good chemical stability and shows small dimensional changes upon redox cycling [30]. It is also observed that the re-oxidation is faster for Ti-substituted CaMnO 3 at high temperatures [22], and additional Fe doping positively influences the reduction reaction rate and broadened the operation window of the OCM to lower temperatures as well as improve microstructural stability during redox cycling [16]. Although Ti-doping does not assist with the known sulfur intolerance of CaMnO 3 [14, 20,21], remedial technologies for reactivation of the poisoned OCM in situ (in the fuel reactor) are already developed [31].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that CaMn 0.875 Ti 0.125 O 3− δ (CMT) is a promising OCM . Furthermore, it has been shown that iron substitution improves the spontaneous release of oxygen (later called chemical looping oxygen uncoupling, CLOU) as well as providing higher conversion and less degradation of the microstructure . The method of manufacturing the OCM is the second decisive factor.…”
Section: Introductionmentioning
confidence: 99%
“…Two types of self‐supported OCMs, based on the promising calcium manganite titanate perovskite were investigated: Ca 0.98 Mn 0.875 Ti 0.125 O 3 (CMT) and Ca 0.98 Mn 0.75 Fe 0.125 Ti 0.125 O 3 (CMTF125) with 12.5 % iron on the B‐site of the perovskite. The performance characteristics of these two materials as OCMs for fluidized‐bed CLC were published separately . CMTF125 was also coated on α‐alumina (CMTF125@alumina).…”
Section: Introductionmentioning
confidence: 99%